2015
DOI: 10.2147/opth.s76406
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis: state of the art

Abstract: Endophthalmitis is an uncommon diagnosis but can have devastating visual outcomes. Endophthalmitis may be endogenous or exogenous. Exogenous endophthalmitis is caused by introduction of pathogens through mechanisms such as ocular surgery, open-globe trauma, and intravitreal injections. Endogenous endophthalmitis occurs as a result of hematogenous spread of bacteria or fungi into the eye. These categories of endophthalmitis have different risk factors and causative pathogens, and thus require different diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 191 publications
(243 reference statements)
3
80
2
2
Order By: Relevance
“…The incidence of endophthalmitis after cataract surgery has been reported to range from 0.03% to 0.2% [ 34 ]. Serial studies from the Bascom Palmer Institute showed a decrease in incidence in the most recent series.…”
Section: Exogenous Endophthalmitismentioning
confidence: 99%
“…The incidence of endophthalmitis after cataract surgery has been reported to range from 0.03% to 0.2% [ 34 ]. Serial studies from the Bascom Palmer Institute showed a decrease in incidence in the most recent series.…”
Section: Exogenous Endophthalmitismentioning
confidence: 99%
“…With the increased numbers of cataract surgeries, pars plana vitrectomies, and anti-vascular endothelial growth factor (VEGF) injections for other ocular diseases, the risk of endophthalmitis associated with these conditions is increasing (63)(64)(65)(66)(67)(68). In the context of blinding eye infections, TLRs have been investigated for their anti-inflammatory therapeutic properties.…”
Section: Fig 9 Proinflammatory Mediator Expression In Tlr4mentioning
confidence: 99%
“…Persistent inflammation and cystoid macular edema (CME) can cause postoperative vision loss [1,2,3 ▪ ]. Infectious endophthalmitis, whereas rare, is another serious vision-threatening complication [4,5,6 ▪▪ ]. Prophylactic therapies are used to reduce the risk of postoperative endophthalmitis, inflammation, and CME, and their development is driven by the need to optimize surgical outcomes without unduly burdening the patient.…”
Section: Introductionmentioning
confidence: 99%